Analise do equilíbrio postural e estabilidade de crianças e adolescentes obesos após protocolo de treinamento funcional de alta intensidade: estudo piloto - Andrade, Manoella Cavalcante de (2022)
Obesity is associated with postural instability, causing obese individuals to have a reduced ability to perform various balance activities, which may increase the risk of falling and may have an impact on confidence in participating in physical activities. High-intensity training is perceived as more enjoyable than continuous moderate-intensity exercise. This can improve exercise adherence and promote health benefits. With the impact generated by the COVID-19 pandemic, telerehabilitation has become an important option for physiotherapists to continue helping and offering rehabilitation services, being an effective tool for the treatment of various diseases, reducing health costs, improving adherence to treatment and quality of life of patients.Objective: To analyze the postural balance behavior of obese children and adolescents in different conditions of stability and vision before and after applying a high-intensity training protocol (HIT) through telerehabilitation. Methods: Pilot study with children and adolescents aged 06 to 17 years with a functional diagnosis of obesity, classified with percentiles between 97 and 99.9 or +2 and +3 z scores by the World Health Organization (WHO) confirmed to the estimates of: Posturography , 3-minute step test (TD3) and body composition, before and after, high-intensity functional training (HIFT). Results: Despite the existence of a significant change in oscillation in the mediolateral (ML) direction on explanatory ground (Eyes open: 4.1±2.1; Eyes closed: 4.7±2.1), in general, children and obese adolescents oscillate in the anteroposterior and mediolateral direction in the same proportion and are more dependent on vision. After the application of the HIFT protocol, there were changes in the COP map responses in the anteroposterior (AP) versus mediolateral (ML) direction, and in the time series in the ellipse area (cm²), length (cm) and mean velocity (cm/s). The number of steps in the step test increased from 77 (66–99) to 89 (75–110) (p≤0.05) after the HIFT Conclusion: Obese children and adolescents sway in an anteroposterior and mediolateral direction in the same proportion and suffer difficulties in maintaining postural control and balance when some sensory information is denied or impaired, as in our case, vision, or when the task is sufficiently challenging, such as changing the support base. They also show that high-intensity functional training (HIFT) through telerehabilitation proved to be an effective tool in promoting the improvement of balance and functional capacity of obese children and adolescents, even though it is not capable of generating effects of improvement in the improvement body.